Divided square difference cordial labeling of some special graphs - Leo, Alfred; Prasad, Vikrama (International Journal of Engineering and Technology, 2018)
In this article, we have introduced the concepts of divided square difference cordial labeling behavior of some special graphs called Jewel graph,Â Wheel graph, Helm graph, Flower graph,Â and Bistar.